Borderland generation : Soviet and Polish Jews under Hitler - Koerber, Jeffrey (Modern Jewish history, 2020)
Raised in the Red City - Vitebsk, 1933 to 1936 -- Responses to Exclusion and Violence - Grodno, 1933 to 1939 -- Red Revolution in Grodno, September 1939 to June 1941 -- Faith in Soviet Security, January 1940 to June 1941 -- Invasion and Holocaust, June to November 1941 -- Exploitation and Annihilation, November 1941-March 1943 -- Survival, 1942 to 1948.